COLLEGE BOTANY VOLUME II - GANGULEE, HIRENDRA CHANDRA; KAR, ASOK KUMAR; SANTRA, S.C. (London New Central Book Agency, 1968)
About the Book: College Botany (Vol. II) The text is updated with the latest facts and figures to cover all plant groups in the most comprehensive and remarkable manner. It is meticulously planned for the undergraduate and postgraduate students of Botany, Plant Sciences, Plant Pathology and Microbiology. The book will be of immense use to the academicians, researchers and to all those who have concern for plant science and allied subject areas. Since 1968, the book has been revised and reprinted several times. About the Authors: H C Gangulee, K S Das, C Datta H C Gangulee, MSc, DSc, FNA; Formerly Professor of Botany, Darjeeling Govt. College; Presidency College
Keywords: Botany; Plant